An Open List of Computer Programming Student’s Common Problems and its Leverage in Teaching Practice - Cortinovis, Renato; Bolton, Pablo Frank; Caceffo, Ricardo (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP), 2023)
Educators are frequently baffled by the problems faced and misconceptions held by their novice programming students. Yet, understanding these problems clearly is fundamental for an educator, both to properly evaluate their students as well as to engage them with suitable pedagogical strategies. This paper describes the development of a comprehensive - although not final - open list of problems commonly experienced by novices, focused on procedural and object oriented programming, and language agnostic and as much conceptual/strategic oriented as possible. It shows how the list can be used to improve the evaluation of students in the teaching practice, with targeted tests and detailed evaluation rubrics. It also shows antipattern cards which not only provide examples on how to detect a specific problem, but also indications on its possible origin, and suggestions for pedagogical strategies to overcome it. The paper finally hints at a strategy to crowdsource a battery of standardised/calibrated tests, that can be used both for the formative and summative evaluation of students, as well as to objectively compare different educational strategies and educational systems.